Jurusan Agroteknologi Fakultas Pertanian Universitas Lampung - Andalasari, Tri Dewi; Nurmiaty, Yayuk; Ginting, Yohannes C; Zahra, Yamatri (Politeknik Negeri Lampung., 2019)
Gladiolus is a potential ornamental plant to be widely developed because its high aesthetic value. Generally, gladiolus is propagated vegetatively by using tuber that called corm. There are some problems in gladiolus vegetative propagation, which is corm has a dormancy period and produces only one to two corms for each gladiolus plant. The effort that can be done to solve these problems is to provide benzyladenine to gladiolus corm. This study aims to determine the response of four varieties of gladiolus (Gladiolus hybridus L.) that soak to benzyladenine in increasing the growth of shoot and corm production. This research was conducted in Bandar Lampung in 2017. The treatment was designed factorially (4 x 4) using Randomized Block Design. The first factor was the varieties of gladiolus ie Anisa, Clara, Nabila, and Nurlaela. The second factor was the 100 ppm concentration of benzyladenine in repeating ie first, second, third, and fourth soaking. Data analysis was tested by Least Significant Difference (LSD) test at 5% level. The results showed that (1) from four gladiolus corm varieties, Nabila produced the highest number of shoots at 10,34 shoots, while the variety that produces the highest number of corm was Clara at 5,71 corms, (2) the benzyladenine that used up to four times for soaking the corm resulted the same response in increasing growth of shoot and corm production of four gladiolus varieties, (3) the response of each gladiolus varieties didn?t depend on how many times that benzyladenine used to soak the corm in increasing the growth of shoot and corm production of four gladiolus varieties.